Implementation of Physical Education Learning Outcomes Assessment in the 2013 Curriculum - Novri Gazali; Romi Cendra; Hafid Dwi Saputra; Ahmad Rahmadani; Feby Elra Perdima (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2022)
Curriculum implementation is one of the most important problems in the curriculum cycle. The purpose of this study was to determine the implementation of the 2013 curriculum in physical education learning in the aspect of assessing learning outcomes at Cendana High School Pekanbaru. This study uses a qualitative research approach, where the researcher is the key instrument. The data collected in this qualitative study was carried out in a natural setting, the data collection techniques were mostly at the time of observation, primary data sources, and interviews and documentation. The research subjects taken in this study were only 1 school principal and 1 physical education teacher at Cendana High School Pekanbaru City. This data analysis includes three stages, namely data reduction, data display, and drawing conclusions. Based on the results of the study, the conclusions obtained in this study are: the teacher has implemented the 2013 curriculum in physical education learning in the aspect of assessing learning outcomes at Cendana High School Pekanbaru City is in accordance with the applicable curriculum, the implementation can be seen based on the RPP compiled mostly based on the 2013 curriculum, the implementation of learning is also good, as can be seen from the learning process that has used a scientific approach and an integrated thematic approach.